Answer:
- 2
Step-by-step explanation:
It's a simple rule, all you are doing is subtracting 2 every time.
Step-by-step explanation:
The formula for a parallelogram is A=Base x Height
So you multiply the base, which is 6, and the height, which is 4.
A=6x4
Hope it helps!
Answer:
No, it isn't.
Step-by-step explanation:
Pythagorean theorem is x^2 + y^2 = z^2.
6^2 + 8^2 = 9^2
36 + 64 = 81
100 = 81
So, it isn't.
Answer:
Step-by-step explanation:
Solution by completing the square for:
x2−12x+9=0
Keep x terms on the left and move
the constant to the right side
by subtracting it on both sides
x2−12x=−9
Take half of the x term and square it
[−12⋅1/2]^2=36
then add the result to both sides
x^2−12x+36=−9+36
Rewrite the perfect square on the left
(x−6)^2=−9+36
and combine terms on the right
(x−6)^2=27
Take the square root of both sides
x−6=±27−−√
Simplify the Radical term (1):
x−6=±3–√3
Isolate the x on the left side and
solve for x (1)
x=6±3–√3
therefore (2)
x=6+3–√3
x=6−3–√3
which becomes
x=11.1962
x=0.803848
Answer:
Multiplying - make sure your answer is in fraction form.
1.4 x 0.8 = 28/25
2.3 x 1.8 =207/50
2.37 x 1.2 =721/250